IMPLEMENTASI METODE UMMI DALAM PEMBELAJARAN AL-QUR’AN KELAS TAHFIDZ DI SDI AL-GHAFFAR MULYOAGUNG DAU KABUPATEN MALANG - Lintang Yahya; Anwar Sa'dullah; Khoirul Asfiyak (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Tahfidz Al-Qur'an is an activity that has the aim to maintains the Qur'an by repeating its reading continuously. Seeing the conditions currently, the more advanced development of the era, the more the memorizers of the Qur'an from all of circles. So that, with the many memorizers of the Qur’an does not mean many people who are fluent in the memorization (Mutqin). These problems encourage researchers to try to solve such problems at SDI Al-Ghaffar Mulyoagung Dau Malang by offering several solutions as contained in the skripsi of the author. The author uses a qualitative research approach with descriptive type. Some qualitative data collection techniques are through observation, interview, and also documentation. The results of the study were to show the memorization conditions at the school. Secondly, the implementation of the ‘Ummi method in student memorization activities through targets, materials, approaches, time and evaluations that have been determined by the School. Lastly, that is to know what are the factors of supporting and inhibiting both internally and externally for students in memorizing the Qur'an.